2013
DOI: 10.3174/ajnr.a3573
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Characteristics of Atherosclerotic Middle Cerebral Arteries on 3T High-Resolution MRI

Abstract: BACKGROUND AND PURPOSE:There are limited studies on the morphologic characteristics of MCA atherosclerotic stenosis. Our aim was to quantitatively assess the remodeling pattern and plaque distribution of atherosclerotic MCAs with 3T high-resolution MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 20 publications
3
71
1
Order By: Relevance
“…A limited report of intracranial wall thickness measurements based on a cadaver study (25) is not relatable because of the younger age of that population and the anticipated specimen shrinkage of up to 30% (26). However, our mean lumen area measurements agree with the results of published data (7,(18)(19)(20). Resolution constraints limit our ability to stratify a narrow range of true wall thickness values, although this can be partly overcome with larger samples (27).…”
Section: Neuroradiology: Mr Imaging Measures Of Intracranial Atheroscsupporting
confidence: 56%
See 1 more Smart Citation
“…A limited report of intracranial wall thickness measurements based on a cadaver study (25) is not relatable because of the younger age of that population and the anticipated specimen shrinkage of up to 30% (26). However, our mean lumen area measurements agree with the results of published data (7,(18)(19)(20). Resolution constraints limit our ability to stratify a narrow range of true wall thickness values, although this can be partly overcome with larger samples (27).…”
Section: Neuroradiology: Mr Imaging Measures Of Intracranial Atheroscsupporting
confidence: 56%
“…disclosed no relevant by our centralized MR imaging reading center, only 10.4% of participants were excluded because of inadequate QC scores despite the older age of this population. The 3D volume acquisition used herein simplifies the MR imaging protocol by including multiple intracranial vessels in one image, a considerable advantage over the 2D techniques typically used for ICAD imaging (10,18,19), which require identification of plaques during imaging and section positioning along inherently curving vessels. Wall thickness measurement error from partial volume averaging increases as image resolution exceeds wall thickness (10) and when anisotropic voxels are oriented oblique to the vessel axis, as is often encountered with 2D imaging of curved intracranial arteries (10,11).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…53 Similarly, intracranial VW-MR imaging has shown that MCA plaque is more common in the ventral (45%) or inferior (32%) parts of the wall than in the superior (14%) or dorsal (9%) parts where branches arise, 54,55 and basilar artery plaque is more common in the ventral part of the wall, which is opposite the origins of the branches. 56 However, some atherosclerotic plaque does arise close to ostia, and VW-MR imaging has confirmed that indeed MCA plaque with associated infarction has more superior wall involvement than plaque without infarction (24% versus 7%).…”
Section: To Determine the Location Of Atherosclerotic Plaque Relativementioning
confidence: 99%
“…3,[15][16][17]21,34,35 However, those studies lacked information regarding the comparison between luminal angiography and HR-MR, which may lead to disputes and confusion regarding the usefulness of HR-MR as an imaging method. Only a few studies have attempted to reveal the usefulness of HR-MR compared with DSA.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Although HR-MR evaluates and differentiates various ICADs with the direct depiction of arterial walls and multicontrast images 6,[14][15][16][17][18][19][20] that may correlate with luminal angiography, 8,21,22 the usefulness and value of HR-MR compared with luminal angiography are still unclear. Only a few studies presented a comparison or correlation between DSA and HR-MR, 8,13,23 and these studies showed a good correlation regarding the degree of stenosis 8,23 and HR-MR features beyond DSA.…”
mentioning
confidence: 99%